Pengaruh Kompetensi Pedagogik Guru Dan Pemanfaatan Media Pembelajaran Terhadap Hasil Belajar Fiqih Di MA Darussalam Krempyang Nganjuk - Moch. Kabibul Asro; Nailal Muna (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2019)
In educational institutions, the teacher is the most important component, where he as an actor, implementer and spearhead of the educational process in terms of education and teaching. The quality of the learning process requires the development of human resource educators, especially the development of teacher competencies, this is an effort to prepare teachers to have various insights, knowledge, skills, and provide confidence to carry out their duties and obligations. In this case, the researcher analyzes Pedagogic Competence and the Use of Learning Media. The methodology in this study uses a quantitative approach and uses double regression analysis of two variables. As for the data collection in this study using a questionnaire to obtain data on pedagogical competence and the use of instructional media. While the method of observation and documentation to obtain information about learning outcomes, populations, samples, and other information needed in research. The results concluded that this study showed that there was no influence between the completeness of learning media variables (X2) and the Fiqh (Y) learning outcomes in MA Darusslam Krempyang Nganjuk.